2022
DOI: 10.1242/jcs.259893
|View full text |Cite
|
Sign up to set email alerts
|

TFK1, a basal body transition fibre protein that is essential for cytokinesis in Trypanosoma brucei

Abstract: In Trypanosoma brucei, transition fibres (TF) form a nine-bladed pattern-like structure connecting the base of the flagellum to the flagellar pocket membrane. Despite the characterization of two TF proteins, CEP164C and TbRP2, little is known about the organization of these fibres. Here, we report the identification and characterization of the first kinetoplastid-specific TF protein named TFK1 (Tb927.6.1180). Bioinformatics and functional domain analysis identified three TFK1 distinct domains: an N-terminal do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Retinitis pigmentosa-2 (RP-2) (Stephan et al, 2007) and TFK1 to the matrix between the TF blades (Ramanantsalama et al, 2022). Our screen identified and confirmed that a further 30 proteins localise to the TFs in trypanosomes, bringing the total to 32.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Retinitis pigmentosa-2 (RP-2) (Stephan et al, 2007) and TFK1 to the matrix between the TF blades (Ramanantsalama et al, 2022). Our screen identified and confirmed that a further 30 proteins localise to the TFs in trypanosomes, bringing the total to 32.…”
Section: Discussionmentioning
confidence: 56%
“…Two TFPs have previously been experimentally confirmed in trypanosomes: retinitis pigmentosa-2 ( Stephan et al, 2007 ) and TFK1, which localises to the matrix between the transition fibre blades ( Ramanantsalama et al, 2022 ). Our screen identified and confirmed that a further 30 proteins localise to the transition fibres in trypanosomes, bringing the total number of TFPs to 32.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Complexity of transition fibres in ciliated eukaryotes Our screen identified and confirmed 30 proteins that localise to the TFs in trypanosomes. Two further TFPs were previously experimentally confirmed in Trypanosomes -Retinitis pigmentosa-2 (RP-2) (Stephan et al, 2007) and TFK1 to the matrix between the TF blades (Ramanantsalama et al, 2022) bringing the current number to 32. This challenges the traditional view that TFs are simple structures comprising only a few proteins and demonstrates that trypanosome TFs are complex structures.…”
Section: Discussionmentioning
confidence: 93%
“…The copyright holder for this preprint (which this version posted May 29, 2023. ; https://doi.org/10.1101/2023.05.29.542710 doi: bioRxiv preprint (Ramanantsalama et al, 2022). Overall in molecular terms, transition fibres have broadly been considered a simple structure comprising only a handful of proteins.…”
Section: Introductionmentioning
confidence: 99%